2004
DOI: 10.1002/ana.20174
|View full text |Cite
|
Sign up to set email alerts
|

Folic acid supplementation enhances repair of the adult central nervous system

Abstract: Folic acid supplementation has proved to be extremely effective in reducing the occurrence of neural tube defects (NTDs) and other congenital abnormalities in humans, suggesting that folic acid can modulate key mechanisms for growth and differentiation in the central nervous system (CNS). To prevent NTDs, however, supplemental folate must be provided early in gestation. This suggests that the ability of folic acid to activate growth and differentiation mechanisms may be confined to the early embryonic period. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
70
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 88 publications
(72 citation statements)
references
References 36 publications
2
70
0
Order By: Relevance
“…In addition, we have previously shown that the combination of peripheral nerve injury and i.p. FA supplementation is additive or synergistic, increasing the number of regenerating axons on the conditioned side nearly 10-fold (7). Accordingly, the SCRM results reported in this study refer to the conditioned side of the spinal cord.…”
Section: Resultsmentioning
confidence: 62%
See 4 more Smart Citations
“…In addition, we have previously shown that the combination of peripheral nerve injury and i.p. FA supplementation is additive or synergistic, increasing the number of regenerating axons on the conditioned side nearly 10-fold (7). Accordingly, the SCRM results reported in this study refer to the conditioned side of the spinal cord.…”
Section: Resultsmentioning
confidence: 62%
“…The SCRM model of spinal cord axonal regeneration combines a sharp bilateral cervical dorsal column transection with a unilateral "conditioning" sciatic nerve injury (spinal cord and sciatic nerve injury [SCSN]) (7,13). Injuring the peripheral axon of the dorsal root ganglia (DRG) enhances growth of both the peripheral (sciatic) and central (dorsal column) components of the DRG (13).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations